Matrine Impairs Platelet Function and Thrombosis and Inhibits ROS Production - Zhang, Sixuan; Gui, Xiang; Ding, Yangyang; Tong, Huan; Ju, Wen; Li, Yue; Li, Zhenyu; Zeng, Lingyu; Xu, Kailin; Qiao, Jianlin (Frontiers in Pharmacology, 2021)
Matrine is a naturally occurring alkaloid and possesses a wide range of pharmacological properties, such as anti-cancer, anti-oxidant, anti-inflammatory effects. However, whether it affects platelet function and thrombosis remains unclear. This study aims to evaluate the effect of matrine on platelet function and thrombus formation. Human platelets were treated with matrine (0-1 mg/ml) for 1 hour at 37°C followed by measuring platelet aggregation, granule secretion, receptor expression by flow cytometry, spreading and clot retraction. In addition, matrine (10 mg/kg) was injected intraperitoneally into mice to measure tail bleeding time, arterial and venous thrombus formation. Matrine dose-dependently inhibited platelet aggregation and ATP release in response to either collagen-related peptide (CRP, 0.1 μg/mL) or thrombin (0.04 U/mL) stimulation without altering the expression of P-selectin, glycoprotein (GP) Ibα, GPVI, or αIIbβ3. In addition, matrine-treated platelets presented significantly decreased spreading on fibrinogen or collagen and clot retraction along with reduced phosphorylation of c-Src. Moreover, matrine administration significantly impaired the in vivo hemostatic function of platelets, arterial and venous thrombus formation. Furthermore, in platelets stimulated with CRP or thrombin, matrine significantly reduced ROS generation and inhibited the phosphorylation level of ERK1/2 (Thr202/Tyr204), p38 (Thr180/Tyr182) and AKT (Thr308/Ser473). In conclusion, matrine inhibits platelet function, arterial and venous thrombosis, possibly involving inhibition of ROS generation, suggesting that matrine might be used as an antiplatelet agent for treating thrombotic or cardiovascular diseases.